2009
DOI: 10.1111/j.1471-4159.2009.06195.x
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase plays a central role in cone cell death in retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) is a collection of diseases in which rod photoreceptors die from a variety of mutations. After rods die, the level of tissue oxygen in the outer retina becomes elevated and there is progressive oxidative damage to cones that ultimately triggers apoptosis. In this study, we investigated the hypothesis that NADPH oxidase (Nox) and/or xanthine oxidase serve as critical intermediaries between increased tissue oxygen and the generation of excessive reactive oxygen species that cause oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 50 publications
1
93
0
1
Order By: Relevance
“…The death of rods is inevitably followed by cone cell death, caused mainly by oxidative damage (36,37). Usui et al reported that generation of excessive ROS caused oxidative damage to cones in the retinal degeneration-1 (rd1+/+) mouse, a model of retinitis pigmentosa (38). A mixture of antioxidants, including α-tocopherol, ascorbic acid, Mn (III) tetrakis (4-benzoic acid) porphyrin, and α-lipoic acid, reduced cone cell death in these rd1+/+ mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…The death of rods is inevitably followed by cone cell death, caused mainly by oxidative damage (36,37). Usui et al reported that generation of excessive ROS caused oxidative damage to cones in the retinal degeneration-1 (rd1+/+) mouse, a model of retinitis pigmentosa (38). A mixture of antioxidants, including α-tocopherol, ascorbic acid, Mn (III) tetrakis (4-benzoic acid) porphyrin, and α-lipoic acid, reduced cone cell death in these rd1+/+ mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…Significant cone ERG responses were not detected in eupatilin-injected rd16 mice at P30 (not shown). Oxidative damage has been suggested as a major contributing factor to cone cell death following the death of rod cells (35). Thus, it is likely that the diminished effect of eupatilin at P30 was due to the secondary death of cone cells.…”
Section: This Suggests That Although Eupatilin Can Promote Ciliogenesmentioning
confidence: 99%
“…NADPH oxidase is known to exist in photoreceptor cells, where it has been linked to retinal degeneration (45)(46)(47). Administration of both agents commenced 1 wk after the onset of diabetes to assure that drug treatment did not influence the severity of diabetes.…”
Section: Methodsmentioning
confidence: 99%